MOTIVASI SEBAGAI PEMEDIASI PENGARUH KOMITMEN DAN LINGKUNGAN KERJA PADA KEPUASAN KERJA - Kustiadi Basuki; Maesaroh Maesaroh (Business Management Journal, 2017)
This study is about "Effects of Commitment and Work Environment on Job Satisfaction With Motivation As an intervening variable in the Hospital Pharmacy Group Partners. Dependent variable in this study is the Job Satisfaction, Intervening variable is the Motivation, And independent variables are Commitment and Work Environment.The number of respondent’s surveyed population in the Hospital Pharmacy Group Partners is 90 employees, but it is taken into the study respondents were 73 employees. The sampling method is a sample random sampling, is sampling technique is done randomly so that each case or element in the population has an equal chance to be selected as the study sample.The study was conducted with several stages. The first stage is to explore the theory of literature or by descriptive statistics and data collection of the researched object. The second stage is to test the feasibility of using the data to test data validity and reliability testing. The third stage is the stage of hypothesis testing using the t test and F test to test the hypothesis either partially or simultaneously. Furthermore, theadjusted coefficient of determination is calculated as well as the formation of the regression equation.The results of this study demonstrate: Commitment is not significant effect on Motivation. Work Environment is significant effect on Motivation. Commitment and Work Environment jointly is significant effect on Motivation. Commitment is not significant effect 2 on Job Satisfaction. Work Environment is significant effect on Job Satisfaction. Motivation is not significantly influence on Job Satisfaction.Commitment, Work Environment and Motivation are significant effect on Job Satisfaction. Intervention Motivation above the influence of Commitment on Job Satisfaction can not add to the strength of the effect of Commitment on Job Satisfaction. Intervention Motivation above the influence of Work Environment on Job Satisfaction can add to the strength of the effect of Work Environment on Job Satisfaction.Keywords: Job Satisfaction, Motivation, Commitment, Work Environment